Anti-angiogenic effects of valproic acid in a mouse model of oxygen-induced retinopathy - Naoto Iizuka; Akane Morita; Chihiro Kawano; Asami Mori; Kenji Sakamoto; Masakazu Kuroyama; Kunio Ishii; Tsutomu Nakahara (Elsevier, 2018)
Pathological retinal angiogenesis contributes to the pathogenesis of several ocular diseases. Valproic acid, a widely used antiepileptic drug, exerts anti-angiogenic effects by inhibiting histone deacetylase (HDAC). Herein, we investigated the effects of valproic acid and vorinostat, a HDAC inhibitor, on pathological retinal angiogenesis in mice with oxygen-induced retinopathy (OIR). OIR was induced in neonatal mice by exposure to 80% oxygen from postnatal day (P) 7 to P10 and to atmospheric oxygen from P10 to P15. Mice were subcutaneously injected with valproic acid, vorinostat, or vehicle once a day from P10 to P14. At P15, retinal neovascular tufts and vascular growth in the central avascular zone were observed in mice with OIR. Additionally, immunoreactivity for phosphorylated ribosomal protein S6 (pS6), an indicator of mammalian target of rapamycin (mTOR) activity, was detected in the neovascular tufts. Both valproic acid and vorinostat reduced the formation of retinal neovascular tuft without affecting vascular growth in the central avascular zone. Valproic acid reduced the pS6 immunoreactivity in neovascular tufts. Given that vascular endothelial growth factor (VEGF) activates mTOR-dependent pathways in proliferating endothelial cells of the neonatal mouse retina, these results suggest that valproic acid suppresses pathological retinal angiogenesis by interrupting VEGF-mTOR pathways. Keywords: Histone deacetylase, Mammalian target of rapamycin, Pathological angiogenesis, Retina, Vascular endothelial growth factor